The Influence of Frame Dependence on Investment Decisions made by Listed Property Fund Managers in South Africa - Lowies, Gert Abraham; ., Christiaan Ernst Cloete (Journal of Economics and Behavioral Studies, 2013)
Behavioural finance describes investors’ and managers’behaviour in terms of their interactions, andhow their behaviour subsequently influences financial and capital markets. One aspect of behavioural finance, frame dependence, reflects the fact that decision-makers may model decisions about problems using subjective frames. Such decisions may lead to errors in judgement. This study’s objective was to determine whether frame dependence influences listed property fund managers in South Africa’s property investment decisions.Therefore, the study examinedquestionsrelating to the disposition effect and loss aversion,as well asfactors influencing selling decisions and the time and difficulty involved in making buying and selling decisions. The study surveyed the fund managers of all South African-based property funds listed on the Johannesburg Securities Exchange (JSE). Non-parametric statistical measures were used.The resultsreveal the presence of the disposition effect and a strong desire to cut losses as a motivating factor to sell a property. In the context of the difficulties associated with, and time spent in, buying new properties, it appears that South African property fund managers are, to some extent, lossaverse. This study recommends that fund managers be alerted to the presence of frame dependence in their decisions, so that they canincorporate it in their normative investment strategies.They need to know that they are loss averse in their investment decision-making, resulting ina possible loss of perfectly positioned, profitable investment opportunities. This study expands the body of knowledge surrounding property investment decision behaviour in an emerging market.